World at one view. - Phelps, Humphrey, 19th cent. (D. Needham, 1847)
Map shows mid-nineteenth century geography, political boundaries, and cities in six continents. Includes tables [populations, cities, religions, building heights, rivers] and illustrations. Insets [Illustrations]: "Panoramic view of the route to China, by the Oregon railroad and the Pacific Ocean. This road once built, would become the great highway of nations," "Mongul," "Mountains of the Eastern Hemisphere," "Malay," "Female costumes of the different parts of the World," "African," [Mountains of the] "Western Hemisphere," "Caucasian," and "Waterspout." Relief shown by hachures. Scale [ca. 1:80,000,000].